2007
DOI: 10.4102/curationis.v30i1.1051
|View full text |Cite
|
Sign up to set email alerts
|

Management of the oral manifestations of HIV/AIDS by traditional healers and care givers

Abstract: In many communities of South Africa, traditional healers are often the only means of health care delivery available. The level of knowledge and ability to recognize oral lesions of 32 traditional healers and 17 care-givers were assessed after a two-day workshop. The data collection instrument was a structured questionnaire, complimented by enlarged clinical photographs of the common oral manifestations of HIV/AIDS. Prior to the workshop, 46 (93.9%) of the 49 respondents had never had any formal information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…Previous research from Ghana and other countries in Africa has shown that TMPs most often claim expertise in visible ailments, such as wounds, snake bites, skin conditions [2830], or locally prevalent diseases such as malaria [3133]. Studies on oral health in sub-Saharan Africa indicate that TMPs identify visible symptoms of oral diseases, such as bleeding gums, but diseases of non-visible signs needed training and hands-on experience [27, 34]. Our study indicates that herbalists tend to lack knowledge of the early stages of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research from Ghana and other countries in Africa has shown that TMPs most often claim expertise in visible ailments, such as wounds, snake bites, skin conditions [2830], or locally prevalent diseases such as malaria [3133]. Studies on oral health in sub-Saharan Africa indicate that TMPs identify visible symptoms of oral diseases, such as bleeding gums, but diseases of non-visible signs needed training and hands-on experience [27, 34]. Our study indicates that herbalists tend to lack knowledge of the early stages of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional healers are considered to be effective agents of change as they command authority in their communities, function as psychologists, marriage and family counselors, physicians and legal and political advisors [7]. They are also the legitimate interpreters of customary rules of conduct, morality and values.…”
Section: Introductionmentioning
confidence: 99%
“…Reaching a consensus on how to merge the objectives of TH with that of the public oral health system could lead to improved equity, increase primary health coverage and may prevent the duplication of functions (Kayombo et al 2007; Wilkinson et al 2007; Rudolph et al 2007). Studies have reported that traditional healers are willing to co-operate with oral health workers in improving the oral health of their patients.…”
Section: Th In Primary Health Care/disease Preventionmentioning
confidence: 99%
“…Masauso Nzima et al (1996) carried out a similar study in four Copperbelt towns in Zambia whereby traditional healer received AIDS training and how to counsel clients on safe sex behaviours, together with follow-up monthly meetings(Masauso Nzima et al 1996). It has been suggested that if TH could identify common oral manifestations of HIV/ AIDS, they can serve as referral points for patients with HIV/AIDS to the main stream health care system (Agbor and Naidoo, 2011, Rudolph et al 2007) and also as oral health counsellors/educators who could identify common dental problems and do the appropriate referrals (Agbor and Naidoo, 2011) and as well educate the community on oral health diseases. …”
mentioning
confidence: 99%